Examining the nature of feedback within the Mini Clinical Evaluation Exercise (Mini-CEX): an analysis of 1427 Mini-CEX assessment forms - Soemantri, Diantha; Dodds, Agnes; Mccoll, Geoff (GMS Journal for Medical Education, 2018)
Background: Despite the growing use, studies have demonstrated some limitations related to the feedback provided in the context of the increasing use of the Mini Clinical Evaluation Exercise (Mini-CEX) in undergraduate medical education. This study examined the written feedback provided on the Mini-CEX form to determine its usefulness as a learning tool for students.Methods: 1427 Mini-CEX assessment forms of final year medical students were collected. Written feedback, both on students’ strength and weakness, was categorized and correlated with the variables of clinical case complexity, assessors’ clinical position and students’ clinical performance rating. Results: The number of general feedback comments for students’ strengths and development were 953 (65.3%) and 604 (38.64%) respectively. Less than 30% of the feedback for each domain was categorized as specific feedback. Significant associations were found between feedback on strength and clinical case complexity (Χ=17.48, <.01); and also with assessor clinical position (Χ=37.10, <.01). There was also an association between feedback for students’ development and assessor clinical position (Χ=27.22, <.01).Conclusion: Based on the Mini-CEX forms of student cohort this study examined, it can be concluded that the written feedback provided in the Mini-CEX assessment form was general and lacked specificity. This finding leads to the need to train clinical teachers in the provision of feedback.